Lingual mucoid cyst in a child: A case report and review of the literature - Ulrich Opoko; Iro Salissou; Ayoub Sabr; Mohamed Raiteb; Faiçal Slimani (Elsevier, 2021)
Mucoid cyst or mucocele is a benign condition affecting mainly the accessory salivary glands in all areas of the oral cavity with a predominance in the lower lip. The literature reports few cases of tongue mucoceles. The aetiologies of mucoceles are still not well elucidated, but some aetiological factors are incriminated such as accidental trauma, as well as partial or total obstruction of the ducts by salivary micro-lithiasis. The clinical signs are not specific and the differential diagnosis is made with other tumours, notably of the accessory salivary glands, a dermoid cyst, a venous angioma, other lesions of the oral mucosa and Blandin-Nuhn mucocele. The definitive diagnosis remains histological. Several treatment options exist, but only surgical treatment is the most recommended with a low recurrence rate. The authors report a case of mucocele of the ventral aspect of the tongue in a 3-year-old girl, treated by surgical removal.